2011
DOI: 10.1007/s11060-011-0634-1
|View full text |Cite
|
Sign up to set email alerts
|

A functional polymorphism in the pre-miR-146a gene is associated with risk and prognosis in adult glioma

Abstract: MicroRNAs (miRNAs) are non-coding RNAs that function as post-transcriptional regulators of tumor suppressors and oncogenes. Single nucleotide polymorphisms (SNPs) in miRNAs may contribute to carcinogenesis by altering expression of miRNAs and their targets. A G>C polymorphism (rs2910164) in the miR-146a precursor sequence leads to a functional change associated with the risk for numerous malignancies. A role for this SNP in glioma pathogenesis has not yet been examined. We investigated whether rs2910164 genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 37 publications
1
58
0
Order By: Relevance
“…As reported previously, deregulated expression of microRNA could be affected by epigenetic mechanisms (DNA methylation and histone modification) (37,38), chromosome deficiency or duplication (38,39), abnormal transcription factors (38,40,41), and disordered microRNA maturation (42,43). The expression of well known tumor suppressors miR-34a and miR-34b/c was directly up-regulated by p53, which may mediate induction of apoptosis, cell cycle arrest, and senescence by p53 (40).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…As reported previously, deregulated expression of microRNA could be affected by epigenetic mechanisms (DNA methylation and histone modification) (37,38), chromosome deficiency or duplication (38,39), abnormal transcription factors (38,40,41), and disordered microRNA maturation (42,43). The expression of well known tumor suppressors miR-34a and miR-34b/c was directly up-regulated by p53, which may mediate induction of apoptosis, cell cycle arrest, and senescence by p53 (40).…”
Section: Discussionmentioning
confidence: 61%
“…These all contribute to the loss of miR-34 expression. A GC polymorphism was reported to be located on the precursor of miR-146a, another well known tumor suppressor, which could alter mature miR-146a expression, and was associated with risk for cervical cancer and adult glioma (42,43). To illuminate the mechanisms contributing to down-regulation of miR-99a in HCC, we computationally mapped CpG islands upstream of the miR-99a gene, but no CpG-enriched region had been found.…”
Section: Discussionmentioning
confidence: 99%
“…The study selection process is shown in Figure 1. Finally, 22 articles (Jazdzewski et al, 2008;Xu et al, 2008;Hoffman et al, 2009;Hu et al, 2009;Tian et al, 2009;Catucci et al, 2010;Guo et al, 2010;Liu et al, 2010;Okubo et al, 2010;Pastrello et al, 2010;Srivastava et al, 2010;Xu et al, 2010;Zeng et al, 2010;Garcia et al, 2011;George et al, 2011;Akkiz et al, 2011;Hishida et al, 2011;Mittal et al, 2011;Permuth-Wey et al, 2011;Yue et al, 2011;Zhou et al, 2011;Zhou et al, 2012) with 11,901 cases and 14,200 controls were included in the present meta-analysis. An article by Catucci et al (2010) reported a case-control study of a German population and an Italian population separately, and one by Jazdzewski et al (2008) reported studies on populations of Finland, Poland, and USA separately.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…The rs2910164 (G/C) polymorphism is a G to C nucleotide change leading to C:U mismatch on the stem region of miR-146a which is one of the variant of miR-146. The compiling evidence indicate that rs2910164 is associated with different types of cancer phenotypes including breast cancer (Shen et al, 2008) gastric cancer Zeng et al, 2010;Kogo et al, 2011), hepatocellular carcinoma (Xu et al, 2008), glioma (Permuth-Wey et al, 2011) prostate and others . The G allele carriers were shown to have higher mature miR-146a synthesis (Xu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%